Examining the Provision of Legal and Religious Education to Islamic Families to Safeguard the Rights and Well-Being of Women and Children: A Case Study Conducted in Malang Regency, East Java - Harry, Musleh; Saifullah, Saifullah; Jundiani, Jundiani; Fajarani, Meisy (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
To this present day, violence against women and children remains prevalent and shows an upward trend over the years. This phenomenon is attributed to a multitude of variables, encompassing both domestic and societal influences. The primary objective of this study is to determine the necessity of legal and religious education inside the family. In addition, it aims to investigate the consequences and potential remedies for the absence of such education in familial settings. This study employs an empirical legal methodology that combines an approach to legislation with the Islamic law. The data was collected through interviews conducted in the city of Malang, East Java and reviews of literature. The study highlights the crucial need for legal and religious education within families due to the persistently high levels of crime. The protection of women in the Islamic law extends from their pre-marital stage through marriage and even after divorce from their spouses. These rights encompass the entitlement to inherit from their parents, access to education, the right to receive love and care when they start a family, provision of bodily and spiritual nourishment, clothing, and a home or place of abode provided by their husbands. Upon divorce, a woman is entitled to receive sustenance, iddah, pastau, mut'ah, and acceptable clothing from her former spouse. Child protection in the Islamic law can be ensured by the provision of nasab (self-identity), radha` (breastfeeding), hadhanah (care and maintenance), walayah (guardianship), and nafaqah (supply of sustenance). The protection of women and children is implemented by proactive measures, such as pre-marital advising and family counseling. Repressive measures, such as issuing threats to abusers, and providing guidance and counseling to victims of violence, are also employed. Proper implementation of women's and children's rights will occur when legal and religious education is conducted within the home environment.